8-Hydroxy-2-deoxy-guanosine identifies oxidative DNA damage in a rural prediabetes cohort - Al-Aubaidy, Hayder A. (Redox Rep, 2013)
Background: Rising levels of oxidative stress play an important role in the pathogenesis of type 2 diabetes mellitus. Therefore, we investigated the serum level of 8-hydroxy-2-deoxy-guanosine (8-OHdG) as an early oxidative stress marker in patients with prediabetes and with type 2 diabetes mellitus. Subjects and methods: Convenience sampling from people attending a diabetes screening clinic. Participants at the rural diabetes screening clinic had their medical history recorded as well as body mass index, blood glucose, cholesterol, glutathione, malondialdehyde, fasting blood glucose and 8-OHdG measured. Statistical analysis was performed using ANOVA followed by Sheffe posthoc test for between-group differences. Results: The 8-OHdG level was significantly greater in the prediabetes (516.5 ± 260 pg/ml) compared to control group (177.8 ± 91 pg/ml; P < 0.01). The diabetes group (1926.9 ± 1197 pg/ml) had the highest level of 8-OHdG, being approximately four times greater compared to the prediabetes group (P < 0.001). No significant change in the cholesterol profile, MDA level indicative of lipid peroxidation and antioxidant activity as measured by erythrocyte reduced glutathione was observed in the prediabetes group compared to the control group (P > 0.05). Conclusions: 8-OHdG levels in both the prediabetes and diabetes group were increased from control values suggesting a role for 8-OHdG as an early disease marker that may be more sensitive compared to cholesterol, MDA and erythrocyte reduced glutathione levels, which were within normal limits. This is of clinical significance as 8-OHdG is a strong indicator of oxidative stress related DNA damage within blood vessel walls and other tissue that increases the risk of cardiovascular disease.